(untitled) (Journal of Mathematics Mechanics and Computer Science, 2023)
In this study, a flat solar collector with a thermosyphon was tested in the laboratory of the Institute of Information and Computing Technologies of the Ministry of Education and Science of the Republic of Kazakhstan, located in Almaty (77 degrees east longitude and 43 degrees north latitude). Experimental data were collected over several sunny and cloudy days. The dynamic response of the system to changes in solar insolation is studied and analyzed. It has been found that such systems can provide enough energy to meet the need for hot water, contrary to the erroneous opinion of local residents. The system operates using six sensors (temperature sensor, water flow sensor, pressure sensor, coolant temperature sensor in the heater tank, coolant temperature sensor in the heat exchanger and outdoor temperature sensor). Six sensors are controlled with a programmable logistics integrated circuit (FPGA) STM32 circuit designed to monitor the entire solar system, and the actuators include power relays. The temperature readings are sent to the ESP 32 module. The ESP 32 module is synchronized with six sensors connected to the STM32 FPGA, with six electrical wires programmed in C++, which after processing the temperature, date and time data received from the real-time clock. After the whole process, all sensor data is sent to the ESP 32 module, where data is sent to the database. During the experiment an electric energy consumption savings of about 1% was achieved due to the control signal in the controller which had a significant impact on the service time of the equipment.